Cytarabine-Induced Encephalitis - Christine Lenfant; Nathalie Greiner; Thierry Duprez (Journal of the Belgian Society of Radiology, 2021)
Teaching Point: Central nervous system adverse effects of cytarabine treatment include aseptic meningitis, myelopathy, and more rarely, encephalopathy, seizures, and cerebellar dysfunction. This case illustrates a cytarabine-induced encephalitis with predominant cerebellar involvement.